Teaching of Hindi and its problems - Бокулевa, Б. С.; Кокеевa, Д. М. (Journal of Oriental Studies, 2017)
The article considered the process of teaching Hindi in Kazakhstan and effective teaching methods, the problems in the teaching of Hindi. The article is written on the basis of personal experience of the author.